An assessment of the competitiveness level of the human resources in science and technology (HRST) of the Department of Science and Technology - Vasquez, Maria Teresa M. (University of the Philippines Diliman, 2010)
The economic landscape of the future is characterized by growing risks and uncertainty. Take for example the financial crisis that only started in the United States and the United Kingdom and yet continued to spill over its effects to other economies including the developing countries. Many countries are now experiencing liquidity shortages, slumping demand for export products, falling commodity prices and significant reductions in foreign investments and remittances, among other things. In today's difficult economic environment, nations that have put in place long-term competitiveness fundamentals remain resilient to weather the storm. Studies on competitiveness of nations are extensively being conducted by two prominent organizations : the World Economic Forum (WEF) and the Institute of Management Development (IMD). The former publishes the annual Global Competitiveness Report while the latter the annual World Competitiveness Yearbook. Competitiveness is defined by the WEF as the set of institutions, policies, and factors that determine the level of productivity of a country. Accordingly, competitive economies tend to be able to produce higher levels of income for their citizens. On the other hand, the IMD views competitiveness as "How nations and businesses are managing the totality of their competencies to achieve greater prosperity". The term "Human resources for science and technology" (HRST) encompasses all personnel engaged in scientific and technological activities. HRST designates a category of highly trained and qualified personnel needed by any country that wishes to conduct scientific and technological activities (S&T). HRST is defined in terms of either qualifications or current occupation. In the former, the appropriate classification is the International Standard Classification of Education (ISCED) fifth, sixth, seventh classes; in the latter, it is the International Standard Classification of Occupations (ISCO) second and third classes (Chou, et al., 2008). The Organization for Economic Cooperation and Development (OECD) classifies research and development (R&D) personnel as only a part of HRST. ISCO 21 defines scientists and engineers as physical, mathematical and engineering science professionals; or life science and health professionals (ISCO 22) . Several studies have been done in evaluating the status of science and technology in the country focusing on areas such as the management of technologies, technology transfer and commercialization, and innovation among other things. Unfortunately, most of these studies fail to take into account the HRST and their capacity to contribute to economic growth and competitiveness of the nation. Cororaton (1999) attributed the very low technological capability of the Philippines to the severe lack of R&D personnel in industry such that with low R&D manpower capable of R&D work, any R&D investments cannot turn into productive results as desired.